Sexting in Serbia – prevalence and relationship with attitudes towards sexuality and sexual risk behaviour - Stanojević, Dragana Z; Antić, Nataša; Radović, Olivera (Sociološki pregled, 2025)
The main aim of this study was to examine the frequency of sexting among students in Serbia, as well as its association with attitudes about sexuality and risky sexual behaviour. The study was conducted on a sample of 227 students, aged 18–28 (M= 23.57, SD= 2.81), 45.4% of whom were male. The obtained data showed that 80.2% of respondents participated in some form of sexting. The most common form is receiving someone else’s personal sexual content, followed by sending one’s own sexual content. Sexual permissiveness is a significant predictor of sending and receiving sexual content, and sex as a sense of togetherness and a tool for achieving goals are predictors of forwarding other people’s content and victimization. Risky sexual behaviour can only be predicted by sexual permissiveness. Attitudes towards sexuality are significant predictors of sexting and risky sexual behaviour, but with a small predictive value.